Facial Abscess due to Staphylococcus aureus in Patient with Type 2 Diabetes Mellitus: Case Report - Dian Galuh Maharani; Hermina Novida (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Diabetes mellitus (DM) is a chronic disease with an increasing frequency over the last decade. DM patient has higher risk of infection than people without diabetes. Several literatures suggest a strong positive correlation between hyperglycemia and skin infections. Skin and soft tissue infections (SSTIs), including abscess which commonly caused by Staphylococcus aureus, could lead to severe and life-threatening infections. The correct diagnosis and effective management therapy should be needed to prevent further complications and reduce morbidity and mortality. We report a case about facial abscess caused by S. aureus in diabetic patient that healed after got incision drainage and antibiotics.